The Utilization of Organic Waste at State Senior High School 3 Muaro Jambi as an Environmentally Friendly Multipurpose Liquid: Pemanfaatan Limbah Organik Di Sma N 3 Muaro Jambi Sebagai Cairan Serbaguna Yang Ramah Lingkungan - Ihsan, Mahya; Adriadi, Ade; Wulandari, Tia; Sazali, Ahmad; Wahyuni, Fitra; Vermita Bestari, Andini; Suprayogi, Dawam (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Waste management has become a central issue due to the growing population and the increasing amount of unmanaged waste. This management should be implemented across all aspects of life, from small to large scales. At the smaller scale, waste management is introduced starting from schools, where values are instilled in students that they will carry into adulthood. The habit of managing waste from an early age is expected to become a positive practice in the future. State Senior High School (SMA N) 3 Muaro Jambi is a well-regarded Senior High School in Jambi Province, holding an A accreditation. Currently, SMA N 3 Muaro Jambi does not have an effective waste management system, particularly for organic waste. Additionally, the school is planning to implement the Adiwiyata program, which includes waste management as one of its key points. This community service activity is carried out in three stages: a survey and analysis of the waste problems, socialization of organic waste management into liquid organic fertilizer as an environmentally friendly solution, and practical training in organic waste management. It is hoped that this activity will provide students with knowledge that can lead to business development, serve as a benchmark for other schools in Jambi Province, and help fulfill the requirements for the Adiwiyata program.